Genetic Programming 12th European Conference, EuroGP 2009 Tübingen, Germany, April, 15-17, 2009 Proceedings - Vanneschi, Leonardo; Gustafson, Steven; Moraglio, Alberto; de Falco, Ivanoe; Ebner, Marc (Theoretical Computer Science and General Issues, 2009)
This book constitutes the refereed proceedings of the 11th European Conference on Genetic Programming, EuroGP 2009, held in Tübingen, Germany, in April 2009 colocated with the Evo* 2009 events. The 21 revised plenary papers and 9 revised poster papers were carefully reviewed and selected from a total of 57 submissions. A great variety of topics are presented reflecting the current state of research in the field of genetic programming, including the latest work on representations, theory, operators and analysis, feature selection, generalisation, coevolution and numerous applications.